2005
DOI: 10.1614/ws-04-085r2
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, translocation, and metabolism of sulfentrazone in peanut, prickly sida (Sida spinosa), and pitted morningglory (Ipomoea lacunosa)

Abstract: Studies were conducted to evaluate uptake, translocation, and metabolism of root-absorbed14C-sulfentrazone in peanut, prickly sida, and pitted morningglory. Peanut absorbed more than five and three times greater14C-sulfentrazone than pitted morningglory and prickly sida, respectively. All plant species translocated appreciable amounts (≥ 39%) of radioactivity to the leaves. The three plant species had some capacity to metabolize14C-sulfentrazone. At 3 h after treatment, 7, 29, and 71% of the radioactivity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In several species, both tolerance and resistance to PPO inhibiting herbicides may occur through different mechanisms, such as those linked to the action site, the increase of the PPO enzyme concentration in the mitochondria (Warabi et al, 2001), the overexpression of genes that encode the PPO enzyme (Jung and Kuk, 2007) and the mutation in the gene encoding the action site (Dayan and Duke, 1997). Among the mechanisms that are not related to the herbicide action site, there is the high translocation associated with rapid metabolization (Eastin, 1971), the reduced absorption (Silva et al, 2007), the high concentration of the glutathione S-transferase enzyme (Frear and Swanson, 1973), the rapid metabolization (Thomas et al, 2005) and the high levels of antioxidants and enzymes that eliminate toxic oxygen species (Duke et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In several species, both tolerance and resistance to PPO inhibiting herbicides may occur through different mechanisms, such as those linked to the action site, the increase of the PPO enzyme concentration in the mitochondria (Warabi et al, 2001), the overexpression of genes that encode the PPO enzyme (Jung and Kuk, 2007) and the mutation in the gene encoding the action site (Dayan and Duke, 1997). Among the mechanisms that are not related to the herbicide action site, there is the high translocation associated with rapid metabolization (Eastin, 1971), the reduced absorption (Silva et al, 2007), the high concentration of the glutathione S-transferase enzyme (Frear and Swanson, 1973), the rapid metabolization (Thomas et al, 2005) and the high levels of antioxidants and enzymes that eliminate toxic oxygen species (Duke et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfentrazone is primarily absorbed by roots and control weeds through protoporphyinogen oxidase (membrane breaking). According to Thomas, Troxler, Smith, Fisher, and Wilcut (2005), studies performed previously indicate that the concentration of sulfentrazone in peanut roots diminishes along the time as it moves to aboveground parts. According to Grey, Dotray, and Grichar (2007), peanut is tolerant to this herbicide due to its metabolization capacity, but lesions as necrosis and growth reduction are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological activity of the hydroxymethyl and carboxylic acid derivatives of sulfentrazone is not known, it has been reported that the methyl group on position 3 of the triazolinone ring is necessary for maximum biological activity and that its replacement by other substituents resulted in 3-to 6-fold decrease in biological activity. Further studies on the metabolism of root-absorbed sulfentrazone in peanut, prickly sida (Sida spinosa), and pitted morning glory (Ipomoea lacunosa) indicated that all plant species are able to metabolize sulfentrazone [29]. One day after treatment, 5%, 27%, and 32% of the radiolabeled sulfentrazone in the shoots of peanut, prickly sida, and pitted morning glory, respectively, was present as unmetabolized sulfentrazone.…”
Section: Metabolism and Selectivity Of Protoporphyrinogen IX Oxidase mentioning
confidence: 99%